Relationship Between Housewives' Knowledge and Mosquito Nest Eradication Efforts in the Wagir Community Health Center Work Area - Natar, Hendrikus Umbu; Masluhiya AF, Swaidatul; Devi, Hilda Mazarina (Poltekkes Kemenkes Aceh, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a significant public health problem in Indonesia, with increasing prevalence rates influenced by various factors, including knowledge and implementation of Mosquito Nest Eradication. While good knowledge is important, it does not always translate directly to a decrease in DHF cases, necessitating the active role of housewives as agents of health behavior change within the family environment. Purpose: To determine the relationship between housewives' knowledge and efforts to eradicate mosquito nests in the Wagir Community Health Center Work Area. Methods: This quantitative correlational study used a cross-sectional design. The study population consisted of 184 housewives, with a sample size of 126 housewives drawn using consecutive sampling. The inclusion criteria included housewives from Sidorahayu Village aged 26-45 years. The instrument used was a questionnaire on knowledge and prevention of mosquito nest eradication. Data analysis used the Spearman rank test. Results: There is a relationship between the knowledge of housewives and efforts to eradicate mosquito nests in the Wagir Health Center Working Area with a p value = 0.000 (p <0.05) accompanied by an r value = 0.704 where the correlation coefficient value shows a strong and positive relationship. Conclusion: There is a significant relationship between housewives' knowledge and mosquito nest eradication efforts in the Wagir Community Health Center work area. Higher housewives' knowledge tends to be followed by better implementation of mosquito nest eradication efforts.